PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN PRODUKSI MIE SAGU BAROKAH DI DESA AIR PUTIH , KECAMATAN BENGKALIS - Dariana, Dariana; Nirwana, Ema; Mz, Irawan Fakhrudin; Ezril, Ezril; Susilawati, Susilawati (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2025)
MSMEs are one of the community's business activities which are a source of strength for the Indonesian economy. However, until now MSMEs are still businesses whose financial performance needs to be improved. Therefore, as one of the foundations of the national economy, MSMEs require maximum empowerment from various parties, especially in managing their financial performance. The aim of this service activity is to provide training and assistance in preparing financial reports for the home industry production of Barokah Sago Noodles in Air Putih Village, Bengkalis District. The result of the activity was an increase in financial literacy knowledge for the Sago Barokah Noodle MSMEs in Air Putih Village, Bengkalis District. Apart from that, this training and mentoring has an impact on improving the financial management of community businesses so that it can encourage the community's economy to improve further